2009
DOI: 10.1016/j.ienj.2008.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Patient participation in emergency care – A phenomenographic study based on patients’ lived experience

Abstract: This is an accepted version of a paper published in International emergency nursing. This paper has been peer-reviewed but does not include the final publisher proofcorrections or journal pagination.Citation for the published paper: Frank, C., Asp, M., Dahlberg, K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
1
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 24 publications
(36 reference statements)
6
73
1
7
Order By: Relevance
“…In line with findings by Berg (2006) and Frank et al (2009), this study shows that the relationship with the patient is essential to provide security and patient participation in the care provided. However, this study also indicates that holism and the creation of individual therapeutic relationships with the patient might be difficult, especially when establishing confidence is linked to a rapid succession of contacts during a series of short encounters.…”
Section: Discussionsupporting
confidence: 90%
“…In line with findings by Berg (2006) and Frank et al (2009), this study shows that the relationship with the patient is essential to provide security and patient participation in the care provided. However, this study also indicates that holism and the creation of individual therapeutic relationships with the patient might be difficult, especially when establishing confidence is linked to a rapid succession of contacts during a series of short encounters.…”
Section: Discussionsupporting
confidence: 90%
“…These results are consistent with earlier studies (Frank et al, 2009;Gordon et al, 2010;Andersson et al, 2012). Our results show that the competencies that facilitate interaction with patients are not a focal point and this is a problem.…”
Section: Discussionsupporting
confidence: 93%
“…This was decisive for the degree of patient influence in the relationship. If the nurse dominated the relationship, the patient did not have much influence, although some studies (Frank et al, 2009b;Haidet, 2006) showed that the patient wanted influence. After 2000, studies revealed that some nurses considered encouraging the patient to participate an important function.…”
Section: The Patient-nurse Relationship -Professional Dominance Restrmentioning
confidence: 99%